Analysis of the Effect of Digital System Integration on Improving Service Quality and Patient Perception at Kabelota Regional Hospital - Latu, Saparuddin; Basir, Muhammad; Rahmaniah, Rahmaniah (Universitas Mandala Waluya, 2025)
In the digital era, hospitals are faced with the challenge of improving service quality by integrating digital systems. Although technologies such as SIMRS have begun to be implemented, there are still many obstacles, such as infrastructure limitations and low patient satisfaction, that have not been resolved. This study aims to analyze the effect of digital system integration on service quality and outpatient perceptions at Kabelota Hospital, Central Sulawesi. The study used an associative quantitative approach with a cross-sectional design and a total sampling technique of 125 outpatients. The results of the analysis show that digital system integration has a significant effect on service quality (ρ = 0.000 < 0.05), patient perception (ρ = 0.000 < 0.05), and service quality also affects patient perception (ρ = 0.000 < 0.05). The conclusion shows the importance of infrastructure development, HR training, and system evaluation for hospital service effectiveness.